2017
DOI: 10.2139/ssrn.3010397
|View full text |Cite
|
Sign up to set email alerts
|

The Impacts of Reduced Access to Abortion and Family Planning Services: Evidence from Texas

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…Because their study uses data from an earlier time in Texas when family planning clinics-and not abortion clinics-closed en masse, their estimates likely reflect the effects of family planning clinic closures. 5 Since we initially released our study, Fischer et al (2017) have released an analysis that also leverages variation induced by Texas HB2. Specifically, they estimate the effects of distance using a similar research design and similarly controling for access to family planning clinics.…”
Section: Texas Hb2 and Its Aftermathmentioning
confidence: 99%
“…Because their study uses data from an earlier time in Texas when family planning clinics-and not abortion clinics-closed en masse, their estimates likely reflect the effects of family planning clinic closures. 5 Since we initially released our study, Fischer et al (2017) have released an analysis that also leverages variation induced by Texas HB2. Specifically, they estimate the effects of distance using a similar research design and similarly controling for access to family planning clinics.…”
Section: Texas Hb2 and Its Aftermathmentioning
confidence: 99%
“…For example, Gerdts and colleagues found that in the wake of HB2, travel distances increased substantially, as did out‐of‐pocket costs for abortion 7 . Meanwhile, Fischer and colleagues found that after passage of the same law, abortions went down by 20% and births increased by 3% in counties that had a distance of 50 or more miles to a provider 17 . Similarly, Lindo et al found that following clinic closures in Texas, an increase of 25 miles in distance to a provider was associated with a 10% drop in the abortion rate 18 .…”
mentioning
confidence: 99%
“…As a result, there is a need for more information regarding changes in the abortion rate associated with changes in abortion supply. In addition, the prior studies that use approaches that plausibly isolate the association between a change in supply and a change in the abortion rate—such as those cited here—are mostly single‐state studies, limiting the generalizability and broader implications of their findings 7–9,17–19 …”
mentioning
confidence: 99%
“…The lay press, medical and legal journals have featured discussions about the impact of these ownership changes on patient care, particularly with regard to reproductive health, such as abortions and sterilizations, and have drawn attention to the $45 billion in federal funding these hospital systems receive each year (Catholics for Choice 2005, National Women's Law Center 2011, Abelson 2012, Mencimer 2013, Martin 2013, Lee and Propublica 2016. This is in addition to other new restrictions on reproductive health care services that proliferated over the past decade (Packham 2017, Quast et al 2017, Fischer, Royer, and White 2017, Cunningham et al 2017, Bailey and Lindo 2018, Lu and Slusky 2016. Existing research on the potential effect of Catholic ownership on patient care has relied on qualitative interviews of patients and doctors (Rubin et al 2006, Stulberg et al 2014.…”
Section: Introductionmentioning
confidence: 98%